Investigation of the Effect of Normal Incidence of RF Wave on Human Head Tissues Employing Cu and Ni Grid PET Films - Pudipeddi, S. S.; Jayasree, P. V. Y. (Engineering, Technology & Applied Science Research, 2022)
The rising number of frequency bands and the demand for wireless communication devices has become a growing concern regarding health and safety. The human head is a vulnerable body part when exposed to mobile phones. To ensure a high level of protection of the head from undesirable Electromagnetic Field (EMF) emissions, a shield is incorporated in this paper between the head and the mobile smartphone. The shielding material used to protect the head from the RF emissions is Copper (Cu) grid transparent Polyethylene Terephthalate (PET) film and Copper (Cu) grid transparent PET film with Nickel (Ni) coating forming a laminated mesh. The RF emission metric from the smartphone is determined to evaluate the Specific Absorption Rate (SAR) numerically with a variation in frequencies ranging from 850MHz to 5.47GHz at normal wave incidence by the Transmission Line Method. The variation in frequency is observed in two head models, one of an adult and one of a child. Compared with the no shield condition, a significant SAR reduction is observed when PET-Cu or PET-Cu-Ni conductive coating transparent shielded mesh is embodied on the front part of the mobile phone between the phone and the head. In the child 7-layered head model at 5.47GHz, a significant reduction in SAR is observed from 10.5W/kg to 0.00001W/kg using the Cu grid PET film and to 0.0000032W/kg using Cu and Ni grid PET film.